2021
DOI: 10.1590/1807-3107bor-2021.vol35.0017
|View full text |Cite
|
Sign up to set email alerts
|

Caries risk assessment in dental practices by dentists from a Brazilian community

Abstract: Data on dental practices related to caries risk assessment (CRA) are scarce among Brazilian dentists. This study aimed to determine the prevalence of CRA use by dentists and factors associated with its use, as well as to quantify dentists' ratings of the importance of specific factors when treatment planning. Dentists registered at the Regional Council of Dentistry of São Paulo State-Araraquara region were sent two paper questionnaires that comprised: a) characteristics of dentists themselves, their practices,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Dental and non-dental health care providers can apply baseline risk categories in predicting caries existence or progression and apply basic prevention treatments to arrest early onset of caries or make referrals to dentists for additional disease management. It has been shown that health care provider risk assessments accurately predict ECC progression ( 10 , 18 ). Some non-dental primary health care providers might even conduct basic therapeutic/preventive treatments such as applying fluoride varnish with necessary supports ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dental and non-dental health care providers can apply baseline risk categories in predicting caries existence or progression and apply basic prevention treatments to arrest early onset of caries or make referrals to dentists for additional disease management. It has been shown that health care provider risk assessments accurately predict ECC progression ( 10 , 18 ). Some non-dental primary health care providers might even conduct basic therapeutic/preventive treatments such as applying fluoride varnish with necessary supports ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some implications for clinical practice should be addressed. In Brazil, only one-third of dentists report using a caries risk assessment tool and only 13% record their assessment in the clinical chart [Tagliaferro et al 2020]. Using the clinical presentation of caries in the primary dentition to indicate caries risk in the permanent dentition represents a simple and practical clinical parameter that requires no additional technology or expense; the dentist needs only identify non-cavitated lesions, which is standard care in pediatric dental practice.…”
Section: Discussionmentioning
confidence: 99%